Novel NGS-Based genomic platform reveals unexploited variability of Prunus persica (L. Batch) for future genetic breeding of peach - Aballay, Maximiliano Martín (2019)
Peach is a diploid (2n=2x=16) specie with a small genome (265Mb), compared to other economically important crops. Due to its self-compatibility and long generation periods, modern peach cultivars have a narrow genetic variability. Therefore novel germoplasms are continuously pursued for breeding purposes. The advance of Next Generation Sequencing (NGS) technologies allows high-throughput genotyping at a reasonable cost but in the case of peach, were scarcely developed. At present, a standard Genotyping By Sequencing (GBS), based in a single restriction with ApekI to reduce genome complexity, was applied in peach. We compared 6 double restrictions with the restriction generated with ApeKI to find that the combination of PstI/MboI retained the highest number of loci in concordance with in silico analysis. With this novel GBS platform, a diverse peach germoplasm collection composed of 190 genotypes was analysed. The libraries were sequenced (HiSeq 1500 Illumina) to obtain a total of 207052814 of paired-end (2x250bp) reads. The mapping against peach genome allowed the identification of 107760 SNP. Phylogenetic and population structure analyses sugested that a group of Bolivian traditional peaches and feral germoplasms of Argentine shares a common origin that probably goes back from the colony period where this specie was introduced in the American continent by the Spanish. Principal Component Analysis (PCA) from genomic data showed that these ancestral germoplasms differ largely from modern peach cultivars. Our results in combination with some outstanding trait of these genotypes (high yield/vigour, pathogen resistance, thermal requirements, etc.) encourage their use in peach breeding programs.